Усереднення початкової і багатоточкової задач для коливних систем із повільно змінними частотами і відхиленим аргументом - Самойленко, А.М.; Петришин, Р.І.; Данилюк, І.М. (Український математичний журнал, 2007)
New theorems on substantiation of the method of averaging over all fast variables on a segment and a semiaxis are proved for multifrequency systems with deviated argument in slow and fast variables. An algorithm for the solution of a multipoint problem with parameters is investigated and an estimate for the difference of solutions of the original and averaged problems is obtained.